Effectiveness of T-Cell Replete Haploidentical Hematopoietic Stem Cell Transplantation for Refractory/Relapsed B Cell Acute Lymphoblastic Leukemia in Children and Adolescents - Sano, Hideki; Mochizuki, Kazuhiro; Kobayashi, Shogo; Ohara, Yoshihiro; Takahashi, Nobuhisa; Kudo, Shingo; Waragai, Tomoko; Ikeda, Kazuhiko; Ohto, Hitoshi; Kikuta, Atsushi (Frontiers in Pediatrics, 2021)
Background: The prognosis of refractory/relapsed B-cell precursor acute lymphoblastic leukemia (BCP-ALL) remains dismal owing to acquired resistance to chemotherapeutic agents. This study aimed to evaluate the efficacy of T-cell replete HLA haploidentical hematopoietic stem cell transplantation (TCR-haplo-HSCT) for pediatric refractory/relapsed BCP-ALL (RR-BCP-ALL). Methods: Nineteen pediatric patients with RR-BCP-ALL underwent TCR-haplo-HSCT between 2010 and 2019 at the Fukushima Medical University Hospital. The disease status at TCR-haplo-HSCT included complete remission (CR) in eight patients and non-CR with active disease in 11 patients. Total body irradiation-based, busulfan-based, and reduced-intensity conditioning regimens were employed in 11, 6, and 2 patients, respectively. Low-dose anti-thymocyte globulin (thymoglobulin, 2.5 mg/kg) was used in all patients. Graft-vs.-host disease (GVHD) prophylaxis was administered with tacrolimus, methotrexate, and prednisolone. Results: All patients received peripheral blood stem cells as the stem cell source. The HLA disparities in graft vs. host directions were 2/8 in one, 3/8 in five, and 4/8 in 13 patients. Among 18 patients who achieved primary engraftment, acute GVHD occurred in all 18 evaluable patients (grade II, 9; grade III, 8; grade IV, 1), and chronic GVHD was observed in 10 out of 15 evaluable patients. Three patients died because of transplant-related mortality. The 3-year overall survival (OS) and leukemia-free survival rates were 57.4 and 42.1%, respectively. Compared to patients older than 10 years in age (N = 10), those younger than 10 years in age (N = 9) showed an excellent OS rate (3-year OS rate: patients < 10 years old, 100%; patients > 10 years old, 20% [95% confidence interval, 3.1–47.5]; p = 0.002). Conclusions: We suggest that TCR haplo-HSCT with low-dose ATG conditioning has the potential to improve the transplantation outcomes in patients with RR-BCP.